Uncovering the neural circuitry involved in the stress-attenuation effects of chewing - Kenichi Sasaguri; Kentaro Yamada; Toshiharu Yamamoto (Elsevier, 2018)
Previous animal studies have indicated that coupling restraint stress load with activation of the masticatory organs (chewing) causes a reduction in the systemic and central nervous system stress response. However, the brain mechanism underlying this effect is unknown. Therefore, in this review, we summarize the literature regarding brain regions involved in the attenuating effects of chewing and the systemic stress response attenuation effects induced by those brain regions. In addition, we also focusing on the amygdala, as the emotional control center, and the hypothalamic-pituitary-adrenal axis, as one of the outputs of the systemic response. In particular, we will report on one of the chewing-related stress attenuation mechanisms within the brain brought about by the activation of the inhibition pathway accompanying the activation of the amygdala's GABAergic function. Keywords: Stress, Chewing, Masticatory organ, Amygdala, GABA